Educational program to improve skills for midwifery interns of a hospital in Lima-Peru 2020 - Campomanes-Pelaez, Elena (2021)
Introduction: The internship in obstetrics is 6 to 10 months, depending on the university. The clinical obstetrician instructors of the high-risk obstetric service (ARO) observed that this variation affected the acquisition of skills required of the interns in the care of obstetric complications. It was decided to implement an educational program for obstetric interns from different universities focused on the acquisition of five basic competencies for the care of obstetric complications. Objective: To introduce the use of educational tools to guarantee the unified clinical instruction of obstetric interns in the ARO rotation, as well as to guide and evaluate the progressive acquisition of basic competencies and skills for the care of obstetric complications. Materials and Methods: Pre-experimental study, carried out in 12 obstetric interns from public and private universities, rotating in a public Hospital. The interns participated in a program to improve clinical skills for obstetric care, checklists and a questionnaire were applied before and after the intervention. The Wilcoxon rank test was applied, after using the Kolmogorv-Smirnov test. Results: Implementation of the use of educational tools considering curricular differences in the training of interns. The level of knowledge of the interns about the 5 basic competencies in the care of obstetric complications was significantly higher at the end of the program. The skills corresponding to the 5 competencies improved significantly, except for one: tocolysis, which could not be implemented with the required frequency in this period. Positive evaluation of the assessment tools by interns and clinical instructors. Conclusions: Obstetric interns require an educational program that allows to unify and improve their obstetric skills and abilities. The educational program can be used as an educational model for the various rotations of the boarding school.